2020
DOI: 10.3390/ijerph17041227
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal Containing Particulate Matter Promotes Th1 and Th17 Inflammatory Response by Monocyte Activation in Organic and Inorganic Compounds Dependent Manner

Abstract: In recent years, a significant increase in the frequency of disorders caused by air pollutants has been observed. Here we asked whether transition metal-containing particulate matter (TMCPM), a component of air pollution, has an effect on the activity of human CD4+ T cell subsets (Th1, Th2, Th17, and Treg). Peripheral blood mononuclear cells (PBMC) from healthy donors were cultured with or without NIST (SRM 1648a—standard urban particulate matter purchased from the National Institute for Standards and Technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…The PM group displayed a very different inflammatory pattern from the LPS group, with the increase in circulating leukocytes and lymphocytes, increased BALF and lung parenchyma macrophages, increased levels of IL-5 in the blood serum, and increased levels of IL-4 and IL-17 in the lung parenchyma. Many studies have shown the connection between the concentration of PM 2.5 and the development or exacerbation of allergies and inflammatory/autoimmune disorders [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The PM group displayed a very different inflammatory pattern from the LPS group, with the increase in circulating leukocytes and lymphocytes, increased BALF and lung parenchyma macrophages, increased levels of IL-5 in the blood serum, and increased levels of IL-4 and IL-17 in the lung parenchyma. Many studies have shown the connection between the concentration of PM 2.5 and the development or exacerbation of allergies and inflammatory/autoimmune disorders [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that exposure to air pollution increases the levels of IL-17 and enhances Th17 differentiation through the aryl hydrocarbon receptor (AHR) [ 31 , 32 ]. Moreover, Gałuszka et al [ 7 ] reported that T cells exposed to transition metal-containing particulate matter showed an increase in the proportion of IFN-γ and IL-17A producing cells, with a concomitant decrease in Treg cells. Our results suggest a Th17/Treg imbalance in our animal exposed to PM 2.5 with increased expression of IL-17 in the lung parenchyma and decreased expression of Foxp3 mRNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finding a cure for a disease even if it is an infectious one, cancer or a neurodegenerative means to find its root cause. The onset and the development of diseases like allergic asthma [35][36][37], multiple sclerosis, Alzheimer and Parkinson diseases or different forms of cancer [38][39][40] for example have been intensely studied in last decades in relation to the toxicity of different pollutants and especially in relation to the emitted air-borne particles less than PM 2.5. Next, we will try to offer some more details about them and about how their toxicity manifests by modulating our immunity.…”
Section: Pollution Landfill Effectsmentioning
confidence: 99%
“…These mediators down-regulate the expression of FoxP3 protein, promoting the inhibition of T reg cells and stimulating pro-inflammatory activity of Th17 lymphocytes. These events lead to an exacerbation of tissue inflammation ( Gałuszka et al, 2020 ; Matthews et al, 2016 ). It is well-known that sunlight prevents respiratory tract infection mediated by several viruses, such as the influenza virus ( Walker and Ko, 2007 ; Tseng and Li, 2005 ).…”
Section: Introductionmentioning
confidence: 99%